Hermeneutics Applied to the Field of Nursing Education - Mora-Escalante, Elena (2014)
The scientific article entitled the hermeneutics applied to the branch of nursing education, it intend to reflect about the challenge posed to the faculty of the School of Nursing at the University of Costa Rica. It was focused on mediating curricular proposal in line with the assumed paradigm. Arises how to understand the training process from hermeneutics, where education is understood as a formation process of the individual from a holistic perspective. It is proposed a pedagogy open to experience and understanding of the subjects whom are actors and the center of the process and as an historical subject, subjective, inter-and intra-subjective seeks dialogue to construct knowledge that is brewing in social and is assimilated and transformed individually. This involves a commitment of teachers to understand the paradigmatic behavior of the curriculum proposal and develop a hermeneutic pedagogy.